The effect of a diet supplement containing S-acetyl-glutathione (SAG) and other antioxidant natural ingredients on glutathione peroxidase in healthy dogs: a pilot study - Francesca Perondi; Donal Bisanzio; Raffaella Adami; Ilaria Lippi; Giorgia Meineri; Monica Isabella Cutrignelli; Selena Massa; Elisa Martello (Italian Journal of Animal Science)
Oxidative stress is common in several human and veterinary conditions and it is associated to alteration of the glutathione peroxidase (GPx) level. GPx is an enzyme present in erythrocytes, kidney, and liver and it has a role in protecting against oxidative damage. In this randomised double-blinded control trial on healthy dogs, we present findings indicating that the administration for a total of 35 days of a supplement containing S-acetyl-glutathione (SAG) alongside other antioxidant natural ingredients, leads to an increase in the GPx level. Furthermore, the supplement positively changes liver blood parameters, even in healthy dogs. These preliminary results hold promise for conducting new studies using the same supplement on dogs affected by liver conditions, thereby confirming its antioxidant effects and the potential improvement of altered blood parameters.HIGHLIGHTS Oxidative stress characterises several conditions in dogs and the use of antioxidants can improve their health. The administration of a new supplement containing S-acetyl-glutathione (SAG) together with other antioxidant natural ingredients, increased the level of glutathione peroxidase (GPx). No adverse events were reported after the supplement administration.